Weather-resistant waterproof coiled material for metal protection and preparation process of weather-resistant waterproof coiled material
By preparing flame-retardant and UV-resistant additives and combining them with modified molybdenum disulfide nanosheets to form a continuous carbon layer and UV protection network, the problem of easy aging and combustion of ordinary polyethylene rolls outdoors is solved, achieving highly efficient UV resistance and flame retardant effects.
Patent Information
- Application Number
- CN202511449071.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-12-09
AI Technical Summary
Existing ordinary polyethylene waterproof membranes are susceptible to UV aging and combustion when used outdoors, making it difficult to meet the UV resistance and flame retardancy requirements of metal components. Furthermore, the uneven addition of traditional flame retardants affects performance.
By preparing flame-retardant additives and UV-resistant additives, the continuous carbon layer and UV protection network are formed by utilizing the phosphorus-nitrogen synergistic flame-retardant mechanism and nanocomposite materials, respectively. Combined with modified molybdenum disulfide nanosheets to form a dense sheet barrier, the flame-retardant and UV-resistant properties of waterproof membranes are improved.
It significantly improves the UV aging resistance and flame retardant properties of waterproof membranes, extends their service life, and meets the specific needs of metal components in various scenarios.
Smart Images

Figure CN121086378A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer waterproofing, specifically to a weather-resistant waterproof membrane for metal protection and its preparation process. Background Technology
[0002] Metal roofing and structures are widely used in industrial buildings, warehousing facilities, and large public buildings due to their advantages such as convenient construction and high strength. However, metal substrates are exposed to the outdoor environment for a long time and are susceptible to erosion by rainwater, which can lead to corrosion. Their joints and connections are also weak points in waterproofing. Therefore, high-performance waterproof membranes have become a key material in metal protection systems.
[0003] Currently, commonly used waterproof membranes for metal protection mainly include bitumen-based membranes, polyvinyl chloride (PVC) membranes, and ordinary polyethylene (PE) membranes. Among them, ordinary polyethylene membranes are increasingly used in the waterproofing field due to their good chemical stability, low-temperature resistance, and processability. However, their resistance to ultraviolet aging is relatively weak, and long-term outdoor use can easily lead to photo-oxidative degradation, resulting in a decline in mechanical properties and damage to waterproof sealing. At the same time, polyethylene materials are flammable and have a low limiting oxygen index. When traditional flame retardants (such as halogenated and inorganic hydroxides) are added, uneven dispersion and poor compatibility with the substrate are likely to occur, which not only affects the mechanical elasticity and waterproof performance of the membrane, but also makes it difficult to meet the flame retardant requirements of metal components in specific scenarios.
[0004] Therefore, there is a need to propose a weather-resistant waterproof membrane for metal protection with anti-ultraviolet aging and flame-retardant properties, as well as its preparation process, in order to extend its service life. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a weather-resistant waterproof membrane for metal protection and its preparation process.
[0006] This invention provides a process for preparing a weather-resistant waterproof membrane for metal protection, comprising the following steps: S1: Preparation of flame retardant additives S1.1: Add 2,4-diamino-6-phenyl-1,3,5-triazine and vanillin to anhydrous ethanol at a ratio of 1 g: (1.6-1.7) g: (25-35) mL, and heat and stir at 65-75 °C for 5-6 h to obtain an intermediate solution; S1.2: Add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above intermediate solution, heat and stir at 75-85℃ for 20-24h, cool naturally to room temperature, filter, wash 2-3 times with hot water at 70-80℃ and toluene respectively, and vacuum dry to obtain flame retardant additive. S2: Preparation of modified molybdenum disulfide nanosheets Molybdenum disulfide in bulk form was prepared into a suspension of molybdenum disulfide nanosheets, and an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide was prepared. Then, the molybdenum disulfide nanosheet suspension was mixed with the aqueous solution of (4-carboxybutyl)triphenylphosphine bromide, and after stirring, centrifugation, washing and drying, modified molybdenum disulfide nanosheets were obtained. S3: Preparation of UV-resistant additives Sodium hydroxide solution was added to titanium tetrachloride solution, stirred and mixed, and then halloysite nanotube dispersion was added to prepare nanocomposite material. After being dispersed in deionized water, nanosheet lignin was added to carry out hydrothermal reaction to obtain anti-ultraviolet additive. S4: Preparation of waterproof membrane Linear high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, polyethylene octene co-elastomer, the above-mentioned UV-resistant additives, the above-mentioned flame-retardant additives, the above-mentioned modified molybdenum disulfide nanosheets, and antioxidant 1010 are added to a mixer for thorough mixing, and then fed into a twin-screw extruder for melt mixing, followed by extrusion, calendering, and freeze setting to obtain a waterproof membrane.
[0007] Furthermore, S2 specifically includes the following steps: S2.1: Add block molybdenum disulfide to N-methylpyrrolidone at a ratio of 1g:(180-200)mL, sonicate for 6-8h, then centrifuge at 4000-5000rpm for 20-30min, and take the supernatant to obtain a molybdenum disulfide nanosheet suspension. S2.2: Add (4-carboxybutyl)triphenylphosphine bromide to deionized water and stir thoroughly to dissolve, to obtain an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide with a concentration of 1.6-1.8 mg / mL; S2.3: Add the above molybdenum disulfide nanosheet suspension to the above (4-carboxybutyl)triphenylphosphine bromide aqueous solution, stir at 200-300 rpm for 2-3 h, then centrifuge at 7000-8000 rpm for 20-30 min, discard the supernatant, wash with deionized water 2-3 times and vacuum dry to obtain modified molybdenum disulfide nanosheets.
[0008] Furthermore, S3 specifically includes the following steps: S3.1: Disperse halloysite nanotubes in deionized water at a ratio of 1g:(45-55)mL, and sonicate for 30-40min to obtain halloysite nanotube dispersion; S3.2: Heat a 2 mol / L titanium tetrachloride solution to 40-50℃, and add a 2 mol / L sodium hydroxide solution while stirring. Continue stirring for 20-30 min, then add the above halloysite nanotube dispersion, and stir at 80-90℃ for 2-3 h. Then adjust the pH to 5 with a 1 mol / L hydrochloric acid solution, and continue stirring for 20-30 min. After filtration, washing and drying, the nanocomposite material is obtained. S3.3: Dissolve the dealkalized lignin in deionized water at a ratio of 1g:(30-40)mL, sonicate for 2-3 hours, freeze dry and grind to obtain nano-sheet lignin; S3.4: Add the above nanocomposite material to deionized water at a ratio of 1g:(30-40)mL, ultrasonically disperse for 20-30min, then add the above nano-sheet lignin, stir for 30-40min, and then hydrothermally react at 125-135℃ for 2-3h. After washing and drying, the UV-resistant additive is obtained.
[0009] Furthermore, the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 2,4-diamino-6-phenyl-1,3,5-triazine is (2.2-2.3):1.
[0010] Furthermore, the mass ratio of (4-carboxybutyl)triphenylphosphine bromide to molybdenum disulfide nanosheets is (1-3):1.
[0011] Furthermore, the amount of sodium hydroxide solution added is twice the volume of the titanium tetrachloride solution.
[0012] Furthermore, the amount of halloysite nanotube dispersion added was four times the volume of the titanium tetrachloride solution.
[0013] Furthermore, the mass ratio of nanosheet lignin to nanocomposite material is 1:(5-6).
[0014] Furthermore, by weight, the raw material composition of the waterproof membrane is as follows: 30-50 parts linear high-density polyethylene, 20-40 parts linear low-density polyethylene, 10-20 parts metallocene polyethylene, 5-15 parts polyethylene octene co-elastomer, 6-8 parts UV-resistant additives, 10-15 parts flame-retardant additives, 3-5 parts modified molybdenum disulfide nanosheets, and 0.5-1 parts antioxidant 1010.
[0015] A weather-resistant waterproof membrane for metal protection, which is prepared by the preparation process of a weather-resistant waterproof membrane for metal protection as described in any one of the above claims.
[0016] The present invention has the following advantages: 1. In this invention, sodium hydroxide solution is first added to titanium tetrachloride solution to generate titanium hydroxide precursor, then halloysite nanotube dispersion is added, and the mixture is heated and stirred to react and form covalent bonds. This allows titanium dioxide nanoparticles to be uniformly loaded onto the surface of halloysite nanotubes, inhibiting the aggregation of nano-titanium dioxide and producing a nanocomposite material. Then, dealkalized lignin is made into a nanosheet structure, which is then tightly bonded to the nanocomposite material under hydrothermal conditions to form a stable UV-resistant additive. This additive is then melt-blended with raw materials such as polyethylene to produce a waterproof membrane. On the one hand, the halloysite nanotubes act as a carrier, fixing the nano-titanium dioxide through covalent bonds, preventing… To prevent aggregation, the introduction of nano-sheet lignin can further improve the dispersibility of nanocomposites in the polyethylene matrix, ensuring uniform distribution of anti-UV additives, forming a continuous UV protection network, and reducing migration. On the other hand, the tubular structure of halloysite nanotubes can "capture" UV light inside the tubes, extending the optical path through multiple reflections, allowing nano-titanium dioxide and the nano-sheet dealkalized lignin attached to the surface of nano-titanium dioxide to absorb more UV light. The unabsorbed UV light is further scattered by the halloysite nanotubes, forming an "absorption-scattering" closed loop, thereby significantly improving the UV aging resistance of waterproof membranes.
[0017] 2. In this invention, 2,4-diamino-6-phenyl-1,3,5-triazine and vanillin are first reacted to generate an intermediate containing two imine bonds. Then, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added to introduce phosphorus, forming a phosphorus-nitrogen synergistic flame retardant additive. After this additive is melt-blended with raw materials such as polyethylene to produce a waterproof membrane, the phosphorus in the flame retardant additive will decompose upon heating to generate acidic substances such as phosphoric acid and polyphosphoric acid, catalyzing the dehydration and carbonization of the waterproof membrane matrix. The reaction forms a continuous and dense char layer on its surface, which can effectively block the transfer of flame heat into the polyethylene interior, preventing the matrix from continuously heating and decomposing, thereby improving the flame retardant performance of the waterproof membrane. At the same time, the alkaline gas produced by the decomposition of the triazine ring in the flame retardant can react with the acidic substances produced by the decomposition of the phosphorus component to generate stable phosphorus and nitrogen compounds (such as ammonium phosphate), which not only reduces the volatilization loss of the phosphorus component, but also further catalyzes the formation of char, thus greatly improving the "flame retardant efficiency per unit mass" of the flame retardant, achieving excellent flame retardant effect without the need for high addition amounts.
[0018] 3. In this invention, after preparing molybdenum disulfide nanosheets from bulk molybdenum disulfide, they are added to an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide. Through electrostatic interaction, (4-carboxybutyl)triphenylphosphine bromide molecules are adsorbed onto the surface of the molybdenum disulfide nanosheets, resulting in modified molybdenum disulfide nanosheets. This modified nanosheets improve the compatibility with the polyethylene matrix. When the modified molybdenum disulfide nanosheets are melt-blended with polyethylene and other raw materials to form a waterproof membrane, the layered nanosheets migrate to the material surface and stack to form a dense "layered barrier," blocking oxygen from reaching the matrix. The phosphorus element in the quaternary phosphine cation introduced on its surface diffuses into the interior of the body. At the same time, the phosphorus element can catalyze the dehydration and cross-linking reaction of the polyethylene matrix at high temperature, promote the formation of the char layer, and thus improve the flame retardant performance of the waterproof membrane. In addition, when modified molybdenum disulfide is used in combination with flame retardant additives, the phosphorus and nitrogen in the flame retardant additives are catalyzed into char through chemical action to form an initial char layer. The layered structure of the modified molybdenum disulfide nanosheets can be embedded in the char layer, fill the gaps in the char layer, and form a "char layer-nanosheet" composite barrier, thereby achieving the effect of synergistically improving the flame retardant performance of the waterproof membrane. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the manufacturing process of the weather-resistant waterproof membrane for metal protection used in an embodiment of the present invention. Detailed Implementation
[0020] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of this invention.
[0021] Example 1: A preparation process for a weather-resistant waterproof membrane for metal protection, such as... Figure 1 As shown, it includes the following steps: S1: Preparation of flame retardant additives S1.1: 2,4-Diamino-6-phenyl-1,3,5-triazine and vanillin were added to anhydrous ethanol at a ratio of 1g:1.6g:25mL, and the mixture was heated and stirred at 65℃ for 5h to obtain an intermediate solution. S1.2: Add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above intermediate solution, heat and stir at 75°C for 20 h, cool naturally to room temperature, filter, wash twice with hot water at 70°C and toluene respectively, and vacuum dry to obtain flame retardant additive, wherein the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 2,4-diamino-6-phenyl-1,3,5-triazine is 2.2:1; S2: Preparation of modified molybdenum disulfide nanosheets S2.1: Add block molybdenum disulfide to N-methylpyrrolidone at a ratio of 1g:180mL, sonicate for 6h, then centrifuge at 4000rpm for 20min, and take the supernatant to obtain a molybdenum disulfide nanosheet suspension. S2.2: Add (4-carboxybutyl)triphenylphosphine bromide to deionized water and stir thoroughly to dissolve, to obtain an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide with a concentration of 1.6 mg / mL; S2.3: The above molybdenum disulfide nanosheet suspension was added to the above (4-carboxybutyl)triphenylphosphine bromide aqueous solution, stirred at 200 rpm for 2 h, then centrifuged at 7000 rpm for 20 min, the supernatant was discarded, and the nanosheets were washed twice with deionized water and vacuum dried to obtain modified molybdenum disulfide nanosheets, wherein the mass ratio of (4-carboxybutyl)triphenylphosphine bromide to molybdenum disulfide nanosheets was 1:1; S3: Preparation of UV-resistant additives S3.1: Disperse halloysite nanotubes in deionized water at a ratio of 1g:45mL, and sonicate for 30min to obtain halloysite nanotube dispersion; S3.2: Heat a 2 mol / L titanium tetrachloride solution to 40°C, and add a 2 mol / L sodium hydroxide solution while stirring. After stirring for 20 min, add the above halloysite nanotube dispersion and stir at 80°C for 2 h. Then adjust the pH to 5 with a 1 mol / L hydrochloric acid solution and continue stirring for 20 min. After filtration, washing and drying, obtain the nanocomposite material. The amount of sodium hydroxide solution added is twice the volume of the titanium tetrachloride solution, and the amount of halloysite nanotube dispersion added is four times the volume of the titanium tetrachloride solution. S3.3: Dissolve the dealkalized lignin in deionized water at a ratio of 1g:30mL, sonicate for 2 hours, freeze dry and grind to obtain nano-sheet lignin; S3.4: Add the above nanocomposite material to deionized water at a ratio of 1g:30mL, ultrasonically disperse for 20min, then add the above nano-sheet lignin, stir for 30min, and then hydrothermally react at 125℃ for 2h. After washing and drying, the UV-resistant additive is obtained, wherein the mass ratio of nano-sheet lignin to nanocomposite material is 1:5. S4: Preparation of waterproof membrane 30 parts by weight of linear high-density polyethylene, 20 parts by weight of linear low-density polyethylene, 10 parts by weight of metallocene polyethylene, 5 parts by weight of polyethylene octene co-elastomer, 6 parts by weight of the above-mentioned UV-resistant additive, 10 parts by weight of the above-mentioned flame-retardant additive, 3 parts by weight of the above-mentioned modified molybdenum disulfide nanosheets, and 0.5 parts by weight of antioxidant 1010 are added to a mixer for thorough mixing, and then fed into a twin-screw extruder for melt mixing. After extrusion, calendering, and freeze setting, a waterproof membrane is obtained.
[0022] Example 2: A preparation process for a weather-resistant waterproof membrane for metal protection, such as... Figure 1 As shown, it includes the following steps: S1: Preparation of flame retardant additives S1.1: 2,4-Diamino-6-phenyl-1,3,5-triazine and vanillin were added to anhydrous ethanol at a ratio of 1 g: 1.65 g: 30 mL, and the mixture was heated and stirred at 70 °C for 5.5 h to obtain an intermediate solution; S1.2: Add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above intermediate solution, heat and stir at 80°C for 22 h, cool naturally to room temperature, filter, wash twice with hot water at 75°C and toluene respectively, and vacuum dry to obtain flame retardant additive, wherein the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 2,4-diamino-6-phenyl-1,3,5-triazine is 2.25:1; S2: Preparation of modified molybdenum disulfide nanosheets S2.1: Add block molybdenum disulfide to N-methylpyrrolidone at a ratio of 1g:190mL, sonicate for 7h, then centrifuge at 4500rpm for 25min, and take the supernatant to obtain a molybdenum disulfide nanosheet suspension. S2.2: Add (4-carboxybutyl)triphenylphosphine bromide to deionized water and stir thoroughly to dissolve, to obtain an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide with a concentration of 1.7 mg / mL; S2.3: The above molybdenum disulfide nanosheet suspension was added to the above (4-carboxybutyl)triphenylphosphine bromide aqueous solution, stirred at 250 rpm for 2.5 h, then centrifuged at 7500 rpm for 25 min, the supernatant was discarded, and the nanosheets were washed twice with deionized water and vacuum dried to obtain modified molybdenum disulfide nanosheets, wherein the mass ratio of (4-carboxybutyl)triphenylphosphine bromide to molybdenum disulfide nanosheets was 2:1; S3: Preparation of UV-resistant additives S3.1: Disperse halloysite nanotubes in deionized water at a ratio of 1g:50mL, and sonicate for 35min to obtain halloysite nanotube dispersion; S3.2: Heat a 2 mol / L titanium tetrachloride solution to 45°C, and add a 2 mol / L sodium hydroxide solution while stirring. After stirring for 25 min, add the above halloysite nanotube dispersion and stir at 85°C for 2.5 h. Then adjust the pH to 5 with 1 mol / L hydrochloric acid solution and continue stirring for 25 min. After filtration, washing and drying, obtain the nanocomposite material. The amount of sodium hydroxide solution added is twice the volume of the titanium tetrachloride solution, and the amount of halloysite nanotube dispersion added is four times the volume of the titanium tetrachloride solution. S3.3: Dissolve dealkalized lignin in deionized water at a ratio of 1g:35mL, sonicate for 2.5h, freeze-dry and grind to obtain nano-sheet lignin; S3.4: The above nanocomposite material was added to deionized water at a ratio of 1g:35mL, ultrasonically dispersed for 25min, and then the above nano-sheet lignin was added. After stirring for 35min, the mixture was hydrothermally reacted at 130℃ for 2.5h. After washing and drying, the UV-resistant additive was obtained. The mass ratio of nano-sheet lignin to nanocomposite material was 1:5.5. S4: Preparation of waterproof membrane 40 parts by weight of linear high-density polyethylene, 30 parts by weight of linear low-density polyethylene, 15 parts by weight of metallocene polyethylene, 10 parts by weight of polyethylene octene co-elastomer, 7 parts by weight of the above-mentioned UV-resistant additive, 12.5 parts by weight of the above-mentioned flame retardant additive, 4 parts by weight of the above-mentioned modified molybdenum disulfide nanosheets, and 0.75 parts by weight of antioxidant 1010 are added to a mixer for thorough mixing, and then fed into a twin-screw extruder for melt mixing. After extrusion, calendering, and freeze setting, a waterproof membrane is obtained.
[0023] Example 3: A preparation process for a weather-resistant waterproof membrane for metal protection, such as... Figure 1 As shown, it includes the following steps: S1: Preparation of flame retardant additives S1.1: 2,4-Diamino-6-phenyl-1,3,5-triazine and vanillin were added to anhydrous ethanol at a ratio of 1g:1.7g:35mL, and the mixture was heated and stirred at 75°C for 6 hours to obtain an intermediate solution. S1.2: Add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above intermediate solution, heat and stir at 85°C for 24 h, cool naturally to room temperature, filter, wash three times with hot water at 80°C and toluene respectively, and vacuum dry to obtain flame retardant additive, wherein the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 2,4-diamino-6-phenyl-1,3,5-triazine is 2.3:1; S2: Preparation of modified molybdenum disulfide nanosheets S2.1: Add block molybdenum disulfide to N-methylpyrrolidone at a ratio of 1g:200mL, sonicate for 8h, then centrifuge at 5000rpm for 30min, and take the supernatant to obtain a molybdenum disulfide nanosheet suspension. S2.2: Add (4-carboxybutyl)triphenylphosphine bromide to deionized water and stir thoroughly to dissolve, to obtain an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide with a concentration of 1.8 mg / mL; S2.3: The above molybdenum disulfide nanosheet suspension was added to the above (4-carboxybutyl)triphenylphosphine bromide aqueous solution, stirred at 300 rpm for 3 h, then centrifuged at 8000 rpm for 30 min, the supernatant was discarded, and the nanosheets were washed three times with deionized water and vacuum dried to obtain modified molybdenum disulfide nanosheets, wherein the mass ratio of (4-carboxybutyl)triphenylphosphine bromide to molybdenum disulfide nanosheets was 3:1; S3: Preparation of UV-resistant additives S3.1: Disperse halloysite nanotubes in deionized water at a ratio of 1g:55mL, and sonicate for 40min to obtain halloysite nanotube dispersion; S3.2: Heat a 2 mol / L titanium tetrachloride solution to 50°C, and add a 2 mol / L sodium hydroxide solution while stirring. After stirring for 30 min, add the above halloysite nanotube dispersion and stir at 90°C for 3 h. Then adjust the pH to 5 with a 1 mol / L hydrochloric acid solution and continue stirring for 30 min. After filtration, washing and drying, obtain the nanocomposite material. The amount of sodium hydroxide solution added is twice the volume of the titanium tetrachloride solution, and the amount of halloysite nanotube dispersion added is four times the volume of the titanium tetrachloride solution. S3.3: Dissolve the dealkalized lignin in deionized water at a ratio of 1g:40mL, sonicate for 3 hours, freeze-dry and grind to obtain nano-sheet lignin; S3.4: Add the above nanocomposite material to deionized water at a ratio of 1g:40mL, ultrasonically disperse for 30min, then add the above nano-sheet lignin, stir for 40min, and then hydrothermally react at 135℃ for 3h. After washing and drying, the UV-resistant additive is obtained, wherein the mass ratio of nano-sheet lignin to nanocomposite material is 1:6. S4: Preparation of waterproof membrane 50 parts by weight of linear high-density polyethylene, 40 parts by weight of linear low-density polyethylene, 20 parts by weight of metallocene polyethylene, 15 parts by weight of polyethylene octene co-elastomer, 8 parts by weight of the above-mentioned UV-resistant additive, 15 parts by weight of the above-mentioned flame-retardant additive, 5 parts by weight of the above-mentioned modified molybdenum disulfide nanosheets, and 1 part by weight of antioxidant 1010 are added to a mixer for thorough mixing, and then fed into a twin-screw extruder for melt mixing, followed by extrusion, calendering, and freeze setting to obtain a waterproof membrane.
[0024] Comparative Example 1 differs from Example 1 in that the UV-resistant additive in step S4 is removed.
[0025] Comparative Example 2 differs from Example 1 in that the UV-resistant additive in step S4 is replaced with an equal amount of nanocomposite material.
[0026] Comparative Example 3 differs from Example 1 in that the flame retardant additive in step S4 is removed.
[0027] Comparative Example 4 differs from Example 1 in that the flame retardant additive in step S4 is replaced with an equal amount of aluminum hydroxide.
[0028] Comparative Example 5 differs from Example 1 in that the modified molybdenum disulfide nanosheets in step S4 are replaced with an equal amount of molybdenum disulfide nanosheets.
[0029] Comparative Example 6 differs from Example 1 in that the modified molybdenum disulfide nanosheets in step S4 are replaced with an equal amount of flame retardant additive.
[0030] Comparative Example 7 differs from Example 1 in that the flame retardant additive in step S4 is replaced with an equal amount of modified molybdenum disulfide nanosheets.
[0031] Test example: Test 1: The UV aging resistance of the waterproof membranes prepared in Examples 1-3 and Comparative Examples 1-2 were tested in parallel three times, and the average value was taken. The results are shown in Table 1.
[0032] Table 1: Test Results of UV Aging Resistance of Waterproof Membrane
[0033] As shown in Table 1 above, in Comparative Example 1, without the addition of UV-resistant additives, the tensile strength retention rate and elongation retention rate of the waterproof membrane after 200 hours of UV aging were significantly lower than those of Example 1. In Comparative Example 2, when the UV-resistant additives were replaced with an equal amount of nanocomposite materials, the tensile strength retention rate and elongation retention rate of the waterproof membrane after 200 hours of UV aging were both higher than those of Comparative Example 1, but still lower than those of Example 1. This indicates that by first adding sodium hydroxide solution to titanium tetrachloride solution to generate titanium hydroxide precursor, then adding halloysite nanotube dispersion, heating and stirring to react, a nanocomposite material is prepared. Then, dealkalized lignin is made into a nanosheet structure, which is then tightly combined with the nanocomposite material under hydrothermal conditions to form a stable UV-resistant additive. After melting and mixing this with raw materials such as polyethylene to prepare a waterproof membrane, the introduction of nanosheet lignin can further improve the dispersibility of the nanocomposite material in the polyethylene matrix, ensure the uniform distribution of the UV-resistant additive, form a continuous UV protection network, reduce migration, and significantly improve the UV aging resistance of the waterproof membrane.
[0034] Test 2: The limiting oxygen index of the waterproof membranes prepared in Examples 1-3 and Comparative Examples 3-7 was tested using an oxygen index meter. The tests were conducted in parallel three times, and the average value was taken. The results are shown in Table 2.
[0035] Table 2: Limiting Oxygen Index Test Results of Waterproof Membranes
[0036] As shown in Table 2 above, the limiting oxygen index of the waterproof membrane prepared in Comparative Example 3 without the addition of flame retardant additives was significantly lower than that in Example 1. This indicates that by first reacting 2,4-diamino-6-phenyl-1,3,5-triazine and vanillin to generate an intermediate containing two imine bonds, and then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to introduce phosphorus, a phosphorus-nitrogen synergistic flame retardant additive is formed. After this additive is melt-blended with raw materials such as polyethylene to produce a waterproof membrane, the flame retardant performance of the waterproof membrane can be effectively improved. In Comparative Example 4, when the flame retardant additive was replaced with an equal amount of ordinary inorganic hydroxide flame retardant (aluminum hydroxide), the limiting oxygen index of the waterproof membrane prepared was also lower than that in Example 1. This shows that the "flame retardant efficiency per unit mass" of this flame retardant additive is higher than that of aluminum hydroxide, and excellent flame retardant effect can be achieved without a high addition amount.
[0037] Furthermore, in Comparative Example 5, the limiting oxygen index of the waterproof membrane obtained without modification of the molybdenum disulfide nanosheets was lower than that of Example 1. This shows that by preparing molybdenum disulfide nanosheets from blocky molybdenum disulfide and adding them to an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide, the (4-carboxybutyl)triphenylphosphine bromide molecules are adsorbed onto the surface of the molybdenum disulfide nanosheets through electrostatic interaction, thus obtaining modified molybdenum disulfide nanosheets. This improves the compatibility of the modified molybdenum disulfide nanosheets with the polyethylene matrix. After the modified molybdenum disulfide nanosheets are melt-blended with raw materials such as polyethylene to form a waterproof membrane, the flame retardant properties of the waterproof membrane can be improved. When only one of the flame retardant additives or modified molybdenum disulfide nanosheets was added in Comparative Examples 6 and 7, the limiting oxygen index of the waterproof membranes was lower than that in Example 1. This shows that modified molybdenum disulfide and flame retardant additives can synergistically improve the flame retardant performance of waterproof membranes.
[0038] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Parts not described in detail in this specification are prior art known to those skilled in the art.
Claims
1. A manufacturing process for a weather-resistant waterproof membrane for metal protection, characterized in that, Includes the following steps: S1: Preparation of flame retardant additives S1.1: Add 2,4-diamino-6-phenyl-1,3,5-triazine and vanillin to anhydrous ethanol at a ratio of 1 g: (1.6-1.7) g: (25-35) mL, and heat and stir at 65-75 °C for 5-6 h to obtain an intermediate solution; S1.2: Add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above intermediate solution, heat and stir at 75-85℃ for 20-24h, cool naturally to room temperature, filter, wash 2-3 times with hot water at 70-80℃ and toluene respectively, and vacuum dry to obtain flame retardant additive. S2: Preparation of modified molybdenum disulfide nanosheets Molybdenum disulfide in bulk form was prepared into a suspension of molybdenum disulfide nanosheets, and an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide was prepared. Then, the molybdenum disulfide nanosheet suspension was mixed with the aqueous solution of (4-carboxybutyl)triphenylphosphine bromide, and after stirring, centrifugation, washing and drying, modified molybdenum disulfide nanosheets were obtained. S3: Preparation of UV-resistant additives Sodium hydroxide solution was added to titanium tetrachloride solution, stirred and mixed, and then halloysite nanotube dispersion was added to prepare nanocomposite material. After being dispersed in deionized water, nanosheet lignin was added to carry out hydrothermal reaction to obtain anti-ultraviolet additive. S4: Preparation of waterproof membrane Linear high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, polyethylene octene co-elastomer, the above-mentioned UV-resistant additives, the above-mentioned flame-retardant additives, the above-mentioned modified molybdenum disulfide nanosheets, and antioxidant 1010 are added to a mixer for thorough mixing, and then fed into a twin-screw extruder for melt mixing, followed by extrusion, calendering, and freeze setting to obtain a waterproof membrane.
2. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 1, characterized in that, S2 specifically includes the following steps: S2.1: Add block molybdenum disulfide to N-methylpyrrolidone at a ratio of 1g:(180-200)mL, sonicate for 6-8h, then centrifuge at 4000-5000rpm for 20-30min, and take the supernatant to obtain a molybdenum disulfide nanosheet suspension. S2.2: Add (4-carboxybutyl)triphenylphosphine bromide to deionized water and stir thoroughly to dissolve, to obtain an aqueous solution of (4-carboxybutyl)triphenylphosphine bromide with a concentration of 1.6-1.8 mg / mL; S2.3: Add the above molybdenum disulfide nanosheet suspension to the above (4-carboxybutyl)triphenylphosphine bromide aqueous solution, stir at 200-300 rpm for 2-3 h, then centrifuge at 7000-8000 rpm for 20-30 min, discard the supernatant, wash with deionized water 2-3 times and vacuum dry to obtain modified molybdenum disulfide nanosheets.
3. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 2, characterized in that, S3 specifically includes the following steps: S3.1: Disperse halloysite nanotubes in deionized water at a ratio of 1g:(45-55)mL, and sonicate for 30-40min to obtain halloysite nanotube dispersion; S3.2: Heat a 2 mol / L titanium tetrachloride solution to 40-50℃, and add a 2 mol / L sodium hydroxide solution while stirring. Continue stirring for 20-30 min, then add the above halloysite nanotube dispersion, and stir at 80-90℃ for 2-3 h. Then adjust the pH to 5 with a 1 mol / L hydrochloric acid solution, and continue stirring for 20-30 min. After filtration, washing and drying, the nanocomposite material is obtained. S3.3: Dissolve the dealkalized lignin in deionized water at a ratio of 1g:(30-40)mL, sonicate for 2-3 hours, freeze dry and grind to obtain nano-sheet lignin; S3.4: Add the above nanocomposite material to deionized water at a ratio of 1g:(30-40)mL, ultrasonically disperse for 20-30min, then add the above nano-sheet lignin, stir for 30-40min, and then hydrothermally react at 125-135℃ for 2-3h. After washing and drying, the UV-resistant additive is obtained.
4. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 1, characterized in that, The mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 2,4-diamino-6-phenyl-1,3,5-triazine is (2.2-2.3):
1.
5. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 2, characterized in that, The mass ratio of (4-carboxybutyl)triphenylphosphine bromide to molybdenum disulfide nanosheets is (1-3):
1.
6. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 3, characterized in that, The amount of sodium hydroxide solution added is twice the volume of the titanium tetrachloride solution.
7. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 3, characterized in that, The amount of halloysite nanotube dispersion added was 4 times the volume of titanium tetrachloride solution.
8. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 3, characterized in that, The mass ratio of nanosheet lignin to nanocomposite material is 1:(5-6).
9. The preparation process of a weather-resistant waterproof membrane for metal protection according to claim 1, characterized in that, By weight, the raw material composition of the waterproof membrane is as follows: 30-50 parts linear high-density polyethylene, 20-40 parts linear low-density polyethylene, 10-20 parts metallocene polyethylene, 5-15 parts polyethylene octene co-elastomer, 6-8 parts UV-resistant additives, 10-15 parts flame-retardant additives, 3-5 parts modified molybdenum disulfide nanosheets, and 0.5-1 parts antioxidant 1010.
10. A weather-resistant waterproof membrane for metal protection, characterized in that, It is prepared by the preparation process of a weather-resistant waterproof membrane for metal protection as described in any one of claims 1-9.